Improving the Management System of Innovative Enterprises in the Context of the Implementation of the Import Substitution Strategy - PARINOV, Denis V.; SHVEDOV, Lev A.; KASYMOVA, Dinara M.; SOLOVIEV, Bogdan A.; OVCHINNIKOV, Alexey P. (Journal of Advanced Research in Law and Economics; Vol 10 No 8 (2019): JARLE Volume X Issue 8(46) Winter 2019, 2019)
Study of the main directions of improving the management system of innovative enterprises in the context of the implementation of the strategy of import substitution. Methodological basis of the study of the problem are the following methods: theoretical (analysis and synthesis of scientific literature and sources, analysis of teaching materials), analysis, synthesis, abstraction, comparison, induction, deduction, modeling, and etc. Studied the role of import substitution for the global economy. The essence and causes of the crisis of the management system of innovative enterprises in the context of the implementation of the strategy of import substitution. The hypothesis that the fundamental priority of improving the system of management of innovative enterprises in the context of the implementation of the import substitution strategy should save an effective management, model management, creating a relationship between the enterprise management system, control its activities, in particular in terms of extension and business and management risks. Studied theoretical aspects of the methodology of management of innovative risks innovative enterprises that implement a strategic initiative in the field of import as the base creation system and the implementation of risk management. Developed a system for the creation and implementation of mechanism of management of innovative risks innovative enterprises that implement a strategic initiative in the field of import for more effective adaptation model save-management as the basis on which to build the system of management of innovative enterprise in the context of the implementation of the strategy of import substitution.